In our time we had few vaccines: Grandparenting as support and strategy towards the immunization of children below the age of five in Ibadan, Nigeria (2023)
The institution of grandparenthood holds an important cultural role as a significant socializing agent for younger generations. Decisions on the care and well-being of new entrants to the family are affected primarily by the views of grandparents. Grandparents’ perspectives impact decision-making on childhood immunization. This study examined grandparents' role in childhood immunization uptake in Ibadan, Nigeria. The study area and population were purposively selected, while qualitative data collection methods were deployed through non-participatory observations and in-depth interviews. A total of 26 in-depth interviews were conducted in three immunisation clinics in the Ibadan metropolis area among public health nurses, parents, and grandparents. The study reveals that grandparenting, as a social institution in Ibadan, places value on the immunisation status of grandchildren. Grandparents perform this social role by educating young parents on the importance of childhood immunisation, among other child-care tips. In many instances, grandparents directly or indirectly monitor their grandchildren’s immunisation appointments and sometimes pay for unsubsidized vaccines that are not on the routine vaccine schedule to ensure the well-being of their direct or indirect grandchildren. In conclusion, the institution of grandparenting enhances childhood immunisation uptake. Grandparents’ involvement in the education of childhood immunisation improves the demand for childhood vaccination and helps achieve timely and complete childhood vaccination. It is, therefore, essential to involve grandparents in interventions for childhood immunization among the study group.